2006
DOI: 10.1080/02841850600557141
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in linburg-comstock anomaly

Abstract: MRI can show localization of the connection in this anomaly and helps the surgeon perform the operation with a limited incision. The operation time is therefore shorter and wound scarring less prominent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
(17 reference statements)
1
6
0
2
Order By: Relevance
“…A similar variation was noticed in 13% of musicians studied by Karalezli et al . The same authors demonstrated that the utility of magnetic resonance imaging in localizing the anomalous tendinous connection in all of their patients (nine) with a clinical diagnosis of the condition, which they advocate, is useful in reduction in surgical time and the degree of scarring, due to the limited incision possible . The usefulness of surgical exploration and release in symptomatic patients of this condition has been well demonstrated …”
supporting
confidence: 63%
“…A similar variation was noticed in 13% of musicians studied by Karalezli et al . The same authors demonstrated that the utility of magnetic resonance imaging in localizing the anomalous tendinous connection in all of their patients (nine) with a clinical diagnosis of the condition, which they advocate, is useful in reduction in surgical time and the degree of scarring, due to the limited incision possible . The usefulness of surgical exploration and release in symptomatic patients of this condition has been well demonstrated …”
supporting
confidence: 63%
“…2 As well as clinical diagnosis, MRI can help confirm and localise the anomalous connection. 11 In our series, whereas some patients had MR scans to exclude other causes of pain, they were not used to determine the location of the anomalous connection.…”
Section: Discussionmentioning
confidence: 97%
“…5,8,9 Steroid treatment does not seem to have longterm benefits, 5,9 and the surgical treatment, although rarely necessary, has shown efficacy. 5,6,8,13 Thus, individuals with intermittent pain may be directed to surgery aimed at reducing the symptomatology and improving the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 High resolution ultrasound examinations and magnetic resonance imaging may help in the confirmation and location of the anomalous interconnection. 13 In symptomatic cases, non-operative management with a splint, oral anti-inflammatory medicines and stretching exercises were not successful regarding long-term clinical improvement. Thus, surgical treatment seems to be the therapy of choice.…”
Section: Introductionmentioning
confidence: 99%